Study of Unnatural Deaths of Women Brought to Raichur Institute of Medical Sciences for Medico-Legal Autopsy - Praveen Kumar (Indian Journal of Forensic Medicine & Toxicology, 2020)
Discrimination against women in our society is deeply embedded within family context of the women. Women are subjected to violence from husbands and from their relatives in their natal as well as marital homes. This study was designed to determine unnatural deaths of females in Raichur during the year 2017. total 362 cases were autopsied where as 77 women of unnatural deaths were autopsied. Third and fourth decade were common age group. Most of the unnatural deaths were suicidal and road traffic accidents. This study reflects the susceptibility of women to unnatural deaths, thus needs to enhance the multipronged protective system, to curb these potentially preventable unnatural deaths of females